2003
DOI: 10.1002/cphc.200390030
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Formic Acid at an Ordered Intermetallic PtBi Surface

Abstract: The electrocatalytic oxidation of formic acid at a PtBi ordered intermetallic electrode surface has been investigated using cyclic voltammetry, rotating disk electrode (RDE) voltammetry and differential electrochemical mass spectrometry (DEMS). The results are compared to those at a polycrystalline platinum electrode surface. The PtBi electrode exhibits superior properties when compared to polycrystalline platinum in terms of oxidation onset potential, current density, and a much diminished poisoning effect by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
187
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(200 citation statements)
references
References 32 publications
8
187
0
5
Order By: Relevance
“…A special focus is on the poisoning of the catalysts by carbon monoxide, and for this, the electrochemical oxidation of formic acid can be studied (see Scheme 1). There are two paths in which formic acid (HCOOH) can be oxidized on the surface of a Pt electrode, namely dehydrogenation and dehydration [6,16]. As shown in Scheme 1, these processes involve either the formation of a reactive intermediate that yields CO 2 as the final product (dehydrogenation) or the formation of CO via the dehydration of formic acid.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…A special focus is on the poisoning of the catalysts by carbon monoxide, and for this, the electrochemical oxidation of formic acid can be studied (see Scheme 1). There are two paths in which formic acid (HCOOH) can be oxidized on the surface of a Pt electrode, namely dehydrogenation and dehydration [6,16]. As shown in Scheme 1, these processes involve either the formation of a reactive intermediate that yields CO 2 as the final product (dehydrogenation) or the formation of CO via the dehydration of formic acid.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…[5]. Furthermore, they have shown that the current densities of PtPb and PtBi electrodes are superior to those of a pure platinum catalyst [6][7][8] and that those intermetallics are almost immune against CO and S poisoning [9,10]. Thus, PtPb and PtBi intermetallic phases are promising materials to replace monometallic platinum nanoparticles in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…This modification can consist in deposition of submonolayer amounts of an element [14][15][16], the deposition of metallic monolayer [17] or the formation of alloys or intermetallic compounds [18][19][20]. These modifications of the platinum can act in two different ways: it can prevent the formation of CO through a third body effect, resulting in an increase in the overall reactivity due to the larger availability of active sites for the active intermediate route, or, it can increase the catalytic activity of the active intermediate route through an electronic effect [21].…”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, the PtPb intermetallic surface did not show the CO stripping oxidation current after CO exposure to the surface. 34 Abruña et al showed that the intermetallic compounds have a high CO tolerance, 32,34 and presumably, the enhanced CO tolerance is attributed to the changes in the Pt-Pt surface interatomic distance of the compounds. The expanded Pt-Pt interatomic distance in the compounds relative to that of the bulk Pt would change the electronic state of the Pt and hinder CO chemisorptions.…”
Section: Introductionmentioning
confidence: 99%